Characterization of the urea-water spray impingement in diesel selective catalytic reduction systems. (1st November 2017) - Liao, Yujun; Dimopoulos Eggenschwiler, Panayotis; Rentsch, Daniel; Curto, Francesco; Boulouchos, Konstantinos
Graphical abstract: Highlights: The spray wall impingement is significant for low pressure sprays. The gas flow entrains or evaporates mainly fine droplets below 90 μm. Impinging liquid undergoes local boiling and forms a film, where urea partly crystalizes. Liquid accumulation leads to solid deposit formation under all conditions investigated. NMR analysis reveals cyanuric acid as the major solid deposit component. Abstract: Exhaust after-treatment selective catalytic reduction (SCR) systems based on urea-water solution are state-of-the-art technologies mitigating NOx emissions for diesel and lean combustion systems. Major challenges for implementing the systems are high NOx reduction performance, uniform mixture formation and solid deposits formation. This study presents a detailed analysis of the urea-water spray wall impingement and influences on reducing agent distribution and deposit formation, thus system performance. High speed images provide detailed information of the impingement process. Moreover, impinging spray mass flux distribution and droplet size distribution have been quantified under typical diesel exhaust flow conditions. The work has been performed with a commercial 3-Hole pressure-driven injector dosing into a flow channel. Under all tested conditions, the impingement is significant. At gas flow conditions of 300 °C, 200 kg/h, 35.6% of the injected fluid impinges on the opposed wall due to entrainment and evaporation. The entrainment level has been found to scale logarithmically with the gas flow momentum, related correlations are provided. Having an integrated analysis of a mechanical patternator and non-intrusive Phase Doppler Anemometry (PDA) results, it is concluded that droplets below 20 μm are completely entrained or evaporated. The impingement rate is gradually increasing with increasing droplet diameter up to 90 μm, while almost all larger droplets reach the opposed wall. High speed imaging shows in detail liquid film formation, film transport, liquid accumulation, nucleate boiling, urea crystallization and melting, as well as thin film evaporation prior to solid deposit formation. The spray impingement leads to liquid film formation. Relevant dimensions have been evaluated with digital image processing. Direct relationship of liquid accumulation to the solid deposit formation has been identified. The permanent solid deposit is consisting of cyanuric acid, biuret, ammelide and ammeline as identified by nuclear magnetic resonance spectroscopy.